P151 The role of bronchoalveolar lavage and its quality in the diagnosis of interstitial lung disease. (15th November 2017) - Ebraheem, A; Macfarlane, L; Booton, R; Chaudhuri, N
Abstract : Background: Bronchoalveolar lavage (BAL) is a widely used diagnostic tool for suspected Interstitial Lung Disease (ILD) patients and is advocated in ILD guidelines. 1 We aimed to evaluate the quality of BAL sampling in the diagnosis of ILD compared to BAL guidelines. 2 Methods: Retrospective cohort study of all BALs performed in ILD at the University Hospital of South Manchester (UHSM) between January 2015 and November 2016. Electronic reports and histopathological cellular analysis were assessed for qualitative outcomes as per BAL guidelines. 2 Results: 416 patients' coded as BAL sampling. 95 (24%) were performed in the diagnostic strategy for ILD. The mean age was 58.9 (range 18–89). 36 (37.9%) were Female and 59 (62.1%) were male.13 (13.7%) had lymphocyte count ≥15%, and 4 (4.2%) had a percentage ≥50%. Eosinophil count was ≥5% in 17 (17.9%), and ≥25% in 2 (2.1%). When assessing quality of samples as per guidelines the percentage of other cells (epithelial/columnar cells) at analysis was more than 5% in 57 (60%) patients. In 37 (38.9%) patients the volume instilled was more than 100 ml. In only 13 (13.7%) patients the volume of fluid retained back was ≥30%of instilled volume. Despite this 76 (80%) patients the volume of fluid obtained for analysis was more than 10 ml. There were no immediate complications reported. 50 (52.6%) of the operators were consultants, 30 (31.6%) were registrars, and in 15 (15.8%) operator was not recorded. Conclusion: The quality of BAL sample is very important for diagnostic accuracy in ILD. Our data shows that BAL performed by general respiratory physicians can be of poor quality. We would advocate adequate training in BAL plus investment in dedicated ILD lists may improve engagement and quality. This data supports the BTS bronchoscopy guidelines in performing regular audit to ensure quality is maintained. Reference: Wells A, Hirani N. Interstitial lung disease guideline. Thorax2008;63(5):v1–v58. Meyer K, Raghu G, Baughman R, et al . An Official American thoracic society clinical practice guideline: The clinical utility of bronchoalveolar lavage cellular analysis in interstitial lung disease. American Journal of Respiratory and Critical Care Medicine 2012;185(9):1004–1014.